Looking (for) patterns: Similarities and differences between infant and adult free scene-viewing patterns - Daan van Renswoude; Maartje EJ Raijmakers; Ingmar Visser (Bern Open Publishing, 2020)
Systematic tendencies such as the center and horizontal bias are known to have a large influence on how and where we move our eyes during static onscreen free scene viewing. However, it is unknown whether these tendencies are learned viewing strategies or are more default tendencies in the way we move our eyes. To gain insight into the origin of these tendencies we explore the systematic tendencies of infants (3 - 20-month-olds, N = 157) and adults (N = 88) in three different scene viewing data sets. We replicated common findings, such as longer fixation durations and shorter saccade amplitudes in infants compared to adults. The leftward bias was never studied in infants, and our results indicate that it is not present, while we did replicate the leftward bias in adults. The general pattern of the results highlights the similarity between infant and adult eye movements. Similar to adults, infants' fixation durations increase with viewing time and the dependencies between successive fixations and saccades show very similar patterns. A straightforward conclusion to draw from this set of studies is that infant and adult eye movements are mainly driven by similar underlying basic processes.